Coexisting nephrotic syndromes influences in st elevation myocardial infarction patient and chronic limb-threatening ischemia patient: is there any correlation? [version 2; peer review: 2 approved] - Jonathan Edbert Afandy; Swastya Dwi Putra; Mikhael Asaf; Suci Indriani; Suko Adiarto; Iwan Dakota; Taofan Taofan; Renan Sukmawan (F1000Research)
Background ST-elevation myocardial infarction (STEMI) and chronic limb-threatening ischemia (CLTI) are severe cardiovascular emergencies requiring urgent intervention. Nephrotic syndrome (NS) increases the risk of arterial thromboembolism (ATE), but its exact contribution remains underrecognized. Case illustration We present three cases of young adults with NS who developed ATE. The first patient had anterior STEMI with high thrombus burden but no significant atherosclerosis, suggesting a thromboembolic event. The second patient, diagnosed with CLTI, had extensive thrombotic occlusions from the infrarenal aorta to the bilateral superficial femoral arteries without atherosclerotic plaques, reinforcing a thromboembolic mechanism. He declined revascularization and was treated with medical therapy, achieving symptom relief. The third patient had CLTI with occlusions in the external iliac and superficial femoral arteries, accompanied by prominent plaque calcification, suggesting an atherosclerotic contribution. He underwent percutaneous transluminal angioplasty with favorable outcomes. Conclusion NS predisposes patients to ATE via hypercoagulability and, in some cases, atherosclerosis. Cardiovascular screening should be prioritized in high-risk patients, and preventive measures, including thromboprophylaxis and lipid management, should be considered. Treatment should be individualized based on the predominant mechanism, with deferred stenting in high thrombus burden STEMI and a multidisciplinary approach for CLTI. Long-term follow-up is essential to prevent recurrence.